Systemic and Ophthalmic Manifestations in Different Types of Refractive Errors in Patients with Down Syndrome - Ljubic, Antonela; Trajkovski, Vladimir; Stankovic, Branislav; Tojtovska, Biljana; Langmann, Andrea; Dimitrova, Galina; Jovanovic, Ivana; Tesic, Milorad (My University, 2022)
Background and Objective: This study aims to investigate the prevalence of systemic and ophthalmic manifestations in different refractive groups in children and young adults with Down syndrome (DS). Materials and Methods: The study was a population-based, cross-sectional study that included 141 Caucasian children and young adults with DS. They were classified into the following three groups: myopia DS group (37 subjects, mean age 15.8 years), emmetropia DS group (41 subjects, mean age 11.7 years) and hyperopia DS group (63 subjects, mean age 10.9 years). The participants underwent inspection, slit-lamp examination, cycloplegic refraction, ocular alignment and ocular motility examination. Ten systemic manifestations were analyzed. Results: There was no difference in the prevalence of any systemic manifestations between the groups. Considering the ophthalmic manifestations, there was statistical difference in the distribution of proportions among the three groups for nystagmus (p = 0.011), iris-stromal atrophy (p = 0.048) and strabismus (p = 0.031). The prevalence of strabismus in our DS myopia group was 35.1%, and in DS hyperopia group 38.1%. Conclusions: The results of our study suggest that DS children and young adults with any refractive error do not have a higher chance of additional systemic manifestations. Myopia in DS was associated with a higher prevalence of nystagmus and iris stromal atrophy, whereas astigmatism was found to be more frequent in hyperopia.